2017
DOI: 10.5222/mmj.2017.050
|View full text |Cite
|
Sign up to set email alerts
|

The smart respiratory monitoring integrated pulmonary index: An overview of the literature

Abstract: GİRİŞAnestezi uygulamalarında hastanın solunum fonksiyonunun doğru olarak değerlendirilmesi büyük önem gösterir. Solunum sayısı (SS) ve arteriyel oksijen satü-rasyonu (SpO 2 ) solunum fonksiyonunun değerlendi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…On the other hand, IPI is a monitoring technique that evaluates both oxygenation and ventilation by delivering noninvasive, dynamic, real-time, and continuous measurements. It reflects the respiratory state with high specificity and sensitivity, allowing for early identification of potential issues [ 12 ]. As it provides real-time monitoring of respiratory parameters, the IPI algorithm could help with decision-making during routine follow-up and recovery, according to a study conducted on patients who underwent electroconvulsive therapy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, IPI is a monitoring technique that evaluates both oxygenation and ventilation by delivering noninvasive, dynamic, real-time, and continuous measurements. It reflects the respiratory state with high specificity and sensitivity, allowing for early identification of potential issues [ 12 ]. As it provides real-time monitoring of respiratory parameters, the IPI algorithm could help with decision-making during routine follow-up and recovery, according to a study conducted on patients who underwent electroconvulsive therapy [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…IPI enables the clinician to assess the patient's respiratory status and determine the need for intervention quickly [ 1 , 10 , 11 ]. In addition, the Food and Drug Administration of the United States (FDA) states that IPI monitors can be used to monitor respiratory parameters in sedated patients [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the studies in the literature, the IPI score has been used to monitor patients' respiratory functions in sedation practices and intensive care [8-10, 16, 17]. In these studies, it was stated that IPI detected the hypoxia event that occurred in the patient during the follow-up and after the procedures with high sensitivity and specificity [10,16]. As understood from the studies in the literature, IPI has been found to easily detect respiratory pathologies in a simple, correct and clear manner.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with ACS were divided into two groups as STEMI and NSTE-ACS. TIMI, HEART, and GRACE risk scores were calculated as indicated in the literature [16,14,15]. The parameters used in all three risk scores consist of the data obtained during the patients ' application to the ED.…”
Section: Test Methodsmentioning
confidence: 99%
“…The interpretation of data obtained from these measurements is an important problem, particularly for healthcare practitioners who are unfamiliar with respiratory monitoring. 5 The integrated pulmonary index (IPI) is calculated by computationally integrating SpO2, EtCO2, RR and HR measurements. This index may be constantly monitored on the patient monitor in numerical or wave form.…”
Section: Introductionmentioning
confidence: 99%